(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Campylobacter species are significant cause of acute gastroenteritis in children and adults, worldwide. Campylobacter jejuni is the predominant species reported, both in developed and developing countries. Stool samples were collected and processed for Campylobacter isolation, identification and antibiotic susceptibility testing. Out of 102 diarrhoeal stool samples collected, of which 8 (7.8%) were Campylobacter species. Among this, 7 (87.5%) were C.jejuni and 1(12.5%) was C.coli. Out of 8 Campylobacter isolates, 6(75%) were from female (75%) and 2 (25%) were from male. Out of 8 isolates predominant resistance were noted with Erythromycin (50%), Ciprofloxacin (37.5 %) & Amoxycillin (25%). 12.5 % resistance observed with Gentamycin, Tetracycline & Ceftriaxone. No resistance observed for Chloramphenicol, Cotrimoxazole. Increase of antibiotic resistance among Campylobacter species is alarming as it limits the therapeutic option for treatment.